Vanuatu : Background Paper. (IMF Staff Country Reports; Country Report, 1996)
This Background Paper on Vanuatu reviews the development of monetary control instruments in five small island economies in the South Pacific (Fiji, Solomon Islands, Tonga, Vanuatu, and Western Samoa) and draws some lessons from their experience. The paper highlights that, except Solomon Islands which have extraordinarily high credit demand from the government, these economies have large structural excess liquidity in the banking system. The paper describes the financial sector in the five economies and analyzes the background for large excess liquidity. It also reviews the developments of monetary instruments in these economies from a comparative perspective.